Researcher Women - Katalin Lipták (DETUROPE)
I think that the equal opportunity and the underprivileged marginal labour-market layers’ significance play an important role in the economics of our days, so the women’s labour-market participation. Analysing the Hungarian data lines, we can see that the women’s labour-market participation significantly lags behind the men’s. I wish to prove with a questionnaire survey that in the North-Hungarian region the women’s labour-market situation and the career opportunities of the researcher women lags behind the men’s slightly. Based on my research, beyond the women’s traditional home tasks have appeared the claims for work derives from the employment, so the double burden is put into practice, too. we can explain with the difficulties of the compatibility of childbearing and the work, the undertaking extra limited tasks of the workplace, providing extra performance which is sensible for the women, that in the North-Hungarian region the female career path move more slowly than the men’s.